Pericardial disease in patients treated with immune checkpoint inhibitors. (14th October 2021) - Gong, J; Drobni, Z D; Zafar, A; Quinaglia, T; Hartmann, S E; Gilman, H K; Raghu, V K; Gongora, C; Alvi, R; Zubiri, L; Nohria, A; Sullivan, R J; et al.
Abstract: Background: There are limited data on the occurrence, associations and outcomes of pericardial effusions and pericarditis after treatment with immune checkpoint inhibitors (ICIs). Purpose: To evaluate incidence of pericardial disease in patients treated with an ICI. Methods: This was a retrospective study at a single academic center that compared 2842 consecutive patients who received ICIs with 2699 age- and cancer-type matched patients with metastatic disease who did not receive ICI (design 1). A pericardial event was defined as a composite outcome of pericarditis and new or worsening moderate or large pericardial effusion. The endpoints were obtained through chart review and were blindly adjudicated. To identify risk factors associated with a pericardial event, in a second analysis, we also compared patients who developed an event on an ICI to patients treated with an ICI who did not develop a pericardial event (design 2). Cox proportional hazard model and logistical regression analysis were performed to study the association between ICI use and pericardial disease as well as pericardial disease and mortality. An additional 6-week landmark analysis was performed to account for lead-time bias. Results: There were 42 pericardial events in the patients treated with ICI (n=2842) over 193 days (interquartile range 64 to 411) with an incidence rate of 1.57 events per 100 person-years. There was a 4-fold increase in the risk for pericarditis or a pericardial effusion among patients on an ICI compared to controls not treated with ICI after adjusting for potential confounders (hazard ratio [HR] 4.37, 95% confidence interval [CI] 2.09–9.14, p<0.001). Patients who developed pericardial disease while on an ICI had a trend for increased all-cause mortality (HR 1.53, 95% CI 0.99–2.36, p=0.05) compared to those who did not develop pericardial disease. When comparing those who developed pericardial disease after ICI treatment to those who did not, a higher dose of corticosteroid pre-ICI (>0.7 mg/kg prednisone) was associated with increased risk of pericardial disease (HR 2.56, 95% CI 1.00–6.57, p=0.049). Conclusions: ICI use was associated with an increased risk for development of pericardial disease among cancer patients and a pericardial event on an ICI was associated with a trend towards increased mortality. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): National Institutes of Health/National Heart, Lung, and Blood Institute; a gift from A. Curt Greer and Pamela Kohlberg